Pendampingan kelompok perikanan di Kecamatan Suruh Kabupaten Semarang - Nurfitriana, Nia; Zaidy, Azam Bachur; Budi, Alfina Syakira; Nurmalia, Nayu (Universitas Halu Oleo, 2025)
Suruh is one of district on Semarang that located in central java and have the potential to fisheries in the fish farming and processing fishery products. The fishing group problems are the basis of purposes consideration are will be achieved this research: (a) Increasing knowledge, attitude, and skill by taking into the number fish farming of the uniformity of seeds spread, the type of feed, and the number of feed doses given and watching the water temperature and ph to improve survival catfishes; (b) Increasing knowledge and attitude of main actor fisheries for partnership in the business process; (c) Increasing knowledge, attitude, and skill processing for using of utilization abon waste to be processed product innovation; (d) Increase knowledge and attitude farming of the catfishes in the application of the groups function as a place of learning and cooperation in developing the business of farming catfishes. Data analysis methods used include technical aspects of fish survival and aspects of fisheries extension evaluation. The Results of extension activities in the Suruh district are 1) Increased knowledge, attitude, and skill aspects in catfishes farming include dempond farming catfishes activities that carried out for 54 days shows the increase 9 %; 2) Increased knowledge and attitude aspects on Pokdakan Ulam Sari. After extension activities, an increasing number of the partnership with efishery. 3) Increased knowledge, attitude, and skill aspects on Poklahsar Mina Rahayu Lestari in processing catfishes skin chips. Abon waste products used to skin catfish chips. 4) Increased knowledge and attitude aspects on Pokdakan Ulam Sari and Poklahsar Mina Rahayu Lestari in group functions